Localization and function of dopamine receptors in the subthalamic nucleus of normal and parkinsonian monkeys - Galvan, Adriana (American Physiological Society, 2014)
The subthalamic nucleus (STN) receives a dopaminergic innervation from the substantia nigra pars compacta, but the role of this projection remains poorly understood, particularly in primates. To address this issue, we used immuno-electron microscopy to localize D1, D2, and D5 dopamine receptors in the STN of rhesus macaques and studied the electrophysiological effects of activating D1-like or D2-like receptors in normal and 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-treated parkinsonian monkeys. Labeling of D1 and D2 receptors was primarily found presynaptically, on preterminal axons and putative glutamatergic and GABAergic terminals, while D5 receptors were more significantly expressed postsynaptically, on dendritic shafts of STN neurons. The electrical spiking activity of STN neurons, recorded with standard extracellular recording methods, was studied before, during, and after intra-STN administration of the dopamine D1-like receptor agonist SKF82958, the D2-like receptor agonist quinpirole, or artificial cerebrospinal fluid (control injections). In normal animals, administration of SKF82958 significantly reduced the spontaneous firing but increased the rate of intraburst firing and the proportion of pause-burst sequences of firing. Quinpirole only increased the proportion of such pause-burst sequences in STN neurons of normal monkeys. In MPTP-treated monkeys, the D1-like receptor agonist also reduced the firing rate and increased the proportion of pause-burst sequences, while the D2-like receptor agonist did not change any of the chosen descriptors of the firing pattern of STN neurons. Our data suggest that dopamine receptor activation can directly modulate the electrical activity of STN neurons by pre- and postsynaptic mechanisms in both normal and parkinsonian states, predominantly via activation of D1 receptors.